The relationship between personality profile and self-care among patients with type 2 diabetes - Dadras, Zahra; Molaei, Behnam; Aghamohammadi, Masoumeh (Frontiers in Psychology, 2022)
Background: As a chronic disease, diabetes needs special self-care behaviors until the end of life. Personality traits are considered to be effective psychological factors in controlling diabetes and self-care in patients with diabetes. The present study was conducted with the aim of determining the relationship between personality profile and self-care among people with type 2 diabetes. Methods: In this descriptive- correlational study, 160 patients with type 2 diabetes referred to the diabetes clinic of Imam Khomeini Educational and Medical Center in Ardabil, 2021 were selected by convenience sampling method. The data collection tools were including Diabetes Self-Care Activities questionnaire (SDSCA) and the short form of Millon Multi-Axis Clinical Test (MCMI-3 which were completed through interviews with patients. Data were analyzed using SPSS software and descriptive statistics (mean, standard deviation and frequency) and inferential statistics (Pearson correlation coefficient and linear regression). Results: Based on the results, apart from obsessive personality disorder, which had a positive relationship with self-care behaviors, a significant negative correlation was observed between schizoid, avoidant, depressed, dependent, antisocial, self-harming, borderline, and paranoid personality disorders with self-care behaviors (p<0.01). Conclusion: The results showed that there is a significant negative relationship between personality profile and self-care status of patients with type 2 diabetes. In other words, a person's personality profile can predict self-care behaviors. Accordingly, personality traits can be considered as one of the influencing factors on self-care in the educational programs of diabetic patients. Holding educational classes in order to empower patients, using psychological interventions and teaching effective solutions can be an effective step towards increasing the level of mental-physical health and self-care of patients with type 2 diabetes.